Comparative study on the effect of oral motor intervention protocols on oral motor skills of preterm infants from tertiary care hospital in metropolitan city: pilot study - Jaywant, Shailaja S.; Kale, Jayashri S. (International Journal of Contemporary Pediatrics, 2020)
Background: Premature infants often have feeding difficulties leading to morbidity or developmental co-morbidities. Premature infant oral motor intervention (PIOMI), has shown the positive effects on feeding progression of the premature infants. PIOMI with the massage technique, may help in improving oral motor activity, weight gain in preterm infants along with better neurobehavioral organization. The study was done to analyse effect of this combined protocol on achieving oral motor control and Neurobehavioral state regulation and evaluate its efficacy against PIOMI. Methods: A total 72 clinically stable infants admitted in premature care unit, fulfilling inclusion criterion were enrolled. They were allocated in control and experimental group. Infants from control group received PIOMI and experimental group received PIOMI with massage therapy (M technique), for 10 minutes each day. Data was collected for oral motor abilities, behavioural assessment, weight and day of achieving full feeds. Results: Gestational age at full feeds was 33.65 weeks and 32.89 weeks in control and experimental groups respectively with ‘p’ value 0.002. The number of days of full feed in experimental group was 3.7 days earlier (p=0.04). Infants from experimental group showed higher oral motor score and more weight gain with significant difference The behavioral regulation in infants of both the groups improved after 8 day. Conclusions: PIOMI with M technique was well tolerated by preterm infants. The modified protocol has resulted in achieving early oral feeds and reducing hospital stay. It has also shown the benefit of behavioural regulation along with better oral motor control.